Microwave-assisted synthesis and characterization of SrMoO4 and SrWO4 nanocrystals - Titipun Thongtem (2018)
SrMoO4and SrWO4nanocrystals have been synthesized using Sr(NO3)2and Na2MeO4(Me = Mo and W) in ethylene glycol by a microwave irradiation method at 50% of 180 W for 20 min. The product phases were detected using X-ray and selected area electron diffractions. They show the body-centered primitive tetragonal structure with the lattice parameters of a = b = 5.4007 Å and c = 12.0330 Å for SrMoO4, and a = b = 5.4274 Å and c = 11.9241 Å for SrWO4. X-ray diffraction patterns of the products, obtained by simulation using CaRIne version 3.1 program, are in accordance with those of the corresponding experiment and International Centre for Diffraction Data. A transmission electron microscope revealed the presence of nanocrystals composing the products, with their sizes in the ranges of 14-40 and 14-38 nm for SrMoO4and SrWO4, respectively. Six different vibrations of ν1(Ag), ν3(Bg), ν3(Eg), ν4(Bg), ν2(Ag), and νf.r.(Ag) were detected using a Raman spectrometer, and the ν3(F2) antisymmetric stretching and ν4(F2) bending modes of [MeO4]2-tetrahedrons using a Fourier transform infrared spectrometer. Photoluminescence emissions of SrMoO4and SrWO4, caused by the1T2→1A1transition of electrons, were detected at 410 and 418 nm, respectively. © 2009 Springer Science+Business Media B.V.